Listeria monocytogenes in foods—From culture identification to whole‐genome characteristics - Osek, Jacek; Lachtara, Beata; Wieczorek, Kinga (Food science & nutrition, 2022)
Listeria monocytogenes is an important foodborne pathogen, which is able to persist in the food production environments. The presence of these bacteria in different niches makes them a potential threat for public health. In the present review, the current information on the classical and alternative methods used for isolation and identification of L. monocytogenes in food have been described. Although these techniques are usually simple, standardized, inexpensive, and are routinely used in many food testing laboratories, several alternative molecular‐based approaches for the bacteria detection in food and food production environments have been developed. They are characterized by the high sample throughput, a short time of analysis, and cost‐effectiveness. However, these methods are important for the routine testing toward the presence and number of L. monocytogenes, but are not suitable for characteristics and typing of the bacterial isolates, which are crucial in the study of listeriosis infections. For these purposes, novel approaches, with a high discriminatory power to genetically distinguish the strains during epidemiological studies, have been developed, e.g., whole‐genome sequence‐based techniques such as NGS which provide an opportunity to perform comparison between strains of the same species. In the present review, we have shown a short description of the principles of microbiological, alternative, and modern methods of detection of L. monocytogenes in foods and characterization of the isolates for epidemiological purposes. According to our knowledge, similar comprehensive papers on such subject have not been recently published, and we hope that the current review may be interesting for research communities. In the current review, classical microbiological methods and rapid techniques based on DNA amplification, immunological principles, or biosensor technology used for Listeria monocytogenes detection and identification in food are described. Furthermore, molecular‐based approaches such as whole‐genome sequence techniques for characteristics and typing of the isolates for epidemiological purposes have been discussed.